Hybrid probe combining MicroLED and neural electrode for precise neural modulation and multi-site recording - Gota Shinohara; Tasuku Kayama; Ayumu Okui; Wataru Oda; Atsushi Nishikawa; Alexander Loesing; Nahoko Kuga; Takuya Sasaki; Hiroto Sekiguchi (Applied Physics Express)
Optogenetics enables precise neural control but is limited by conventional optical fibers in complex networks. We present a hybrid device integrating multi-point micro-light-emitting diodes (MicroLEDs) with neural electrodes for localized light stimulation and simultaneous neural recording. Fabricated via direct bonding, it ensures optimal alignment for high spatial-temporal resolution. The thin MicroLED probes minimize invasiveness while maintaining optical performance. Validated in mouse brain models, the system achieves selective neural activation and recording with minimal thermal effects. This scalable, flexible tool overcomes integration challenges, advancing optogenetic research and opening avenues for exploring neural dynamics and targeted neurological therapies.